Second-order tunneling of two interacting bosons in a driven triple well - Zheng Zhou; Wenhua Hai; Qiongtao Xie; Jintao Tan (New Journal of Physics, 2013)
In this study we have investigated the quantum tunneling of two repulsive bosons in a triple-well potential, subject to a high-frequency driving field. By means of the multiple-time-scale asymptotic analysis, we evidence a far-off-resonant strongly interacting regime in which the dominant tunneling of doublons (paired states) is a second-order process and the selected coherent destruction of tunneling occurs either between doublons or between unpaired states. Two Floquet quasienergy bands of both kinds of states are given analytically, where a fine structure up to the second-order corrections is displayed. The analytical results are confirmed numerically, based on the exact model, and may be particularly relevant to controlling correlated tunneling in experiments.